Interpretación de la rigidez lateral en escaleras para el balance torsional aproximado en configuraciones estructurales de edificaciones de concreto reforzado - Salazar Moreano, Andrés Fabián (2020)
This research presents the interpretation of lateral stiffness in stairs for approximate torsional balance in structural configurations of reinforced concrete buildings in order to determine the lateral stiffness in stairs to be included in the torsional balance analysis. Determining the most common type of staircase used in buildings in the city of Riobamba, to later apply the dimensioning of the staircase and to proceed to the calculation of the lateral stiffness of the same one by means of calculation processes by direct assembly and by means of the compatibility matrix A. We continue with the static condensation of the stiffness matrix for two mathematical models that are presented, being the first one an embedded-supported system and the second one a supported-supported system, giving an equation with which to directly calculate the lateral stiffness of the staircase and including it in the analysis of the torsional balance of a proposed building, by means of the center of masses and rigidity, reaching the conclusion that it is possible to include the lateral rigidity of the staircase in the calculation of the center of rigidity of the building, within the dimensioning of the structural configuration of a building.